Treatment for renovascular hypertension due to fibromuscular dysplasia of renal arteries with renal autotransplantation. - Cruzado-Vega, Leónidas; Hernández-Jaras, Julio; Martín-Abad, Leonor; Alonso-Gorrea, Manuel; Miralles-Hernández, Manuel (Nefrología, 2013)
The article presents a case study of a 59-year-old female with a history of chronic iron deficiency anaemia, obstructive sleep apnoea syndrome and dyslipidaemia. The electrocardiogram revealed signs of left ventricular hypertrophy which was not affirmed by Doppler echocardiography. Imaging studies revealed the presence of two cysts located in the upper pole and it was impossible to visualize the left kidney.